Physicochemical Characteristics of Clay Mineral from Ikpeshi in Akoko-Edo Local Government Area, Edo State, Nigeria - E. A. Oyedoh; G. A. Okwah; F. O. Oshomogho (Journal of Applied Sciences and Environmental Management, 2023)
Clay mineral has become increasingly relevant for industrial application due to its environmentally friendly properties, low cost, and relative abundance. Several solid mineral deposits could be found in Edo State of Nigeria. This study therefore, examined the physicochemical characteristics of clay mineral from Ikpeshi in Akoko-Edo Local Government Area, Edo State, Nigeria using various standard techniques. Results obtained reveal that the sample was kaolinite with SiO2 45.116wt%, and Al2O 20.39wt% as the most predominant elements. Wavenumbers of 909.47043cm-1 to 998.92654cm-1 with bold peaks revealed the presence of SiO4-4. The study revealed that the clay from Ikpeshi has kaolinite characteristics and strong thermal stability suitable for lining furnace kilns.